Capacity and consent: Knowledge and practice of legal and healthcare standards. (February 2019) - Lamont, Scott; Stewart, Cameron; Chiarella, Mary
Introduction: Healthcare practitioners have a legal, ethical and professional obligation to obtain patient consent for all healthcare treatments. There is increasing evidence which suggests dissonance and variation in practice in assessment of decision-making capacity and consent processes. Aims: This study explores healthcare practitioners' knowledge and practices of assessing decision-making capacity and obtaining patient consent to treatment in the acute generalist setting. Methods: An exploratory descriptive cross-sectional survey design, using an online questionnaire, method was employed with all professional groups invited via email to participate. Data were collected over 3 months from July to September 2015. Survey content and format was reviewed by the liaison psychiatry team and subsequently contained five sections (demographics, general knowledge and practice, delirium context, legal aspects and education/training). Descriptive, univariate and bivariate analysis of quantitative data and qualitative content analysis of qualitative data were undertaken. Ethical considerations: The study was approved by the institutional Human Research and Ethics Committee and informed consent was taken to be provided by participants upon completion and submission of the de-identified survey. Results: In total, 86 participants engaged the survey with n = 24, exiting at the first consent question. Almost two-thirds of respondents indicated that all treatments required patient consent. Knowledge of consent and decision-making capacity as legal constructs was deficient. Decision-making capacity was primarily assessed using professional judgement and perceived predominantly as the responsibility of medical and psychology staff. A range of patient psychological and behavioural symptoms were identified as indicators requiring assessment of decision-making capacity. Despite this, many patients with delirium have their decision-making capacity assessed and documented only sometimes. Uncertain knowledge and inconsistent application of legislative frameworks are evident. Many participants were unsure of the legal mechanisms for obtaining substitute consent in patients with impaired decision-making capacity and refusing treatment. Conclusion: The legal context of decision-making capacity and consent to treatment appears complex for healthcare practitioners. Professional, ethical and legal standards of care in this context can benefit from structured education programmes and supportive governance processes. An understanding of why 'duty of care' is being used as a framework within the context of impaired decision-making capacity is warranted, alongside a review of the context of Duty of Care within health policy, guidance and faculty teaching.